THE CONSUMER’S ATTITUDES TOWARDS WEB ADVERTISING ON TOURISM MALAYSIA WEB ADVERTISEMENT: LITERATURE REVIEW AND HYPOTHESIS - Bahtiar Mohamad; NurSyuhadaRahimi .; ShamsuDauda Abdu (Journal of Management and Business, 2016)
Advertising has grown exponentially over the last 10 years. In general, advertising can be defined as the activity of a profession of producing information for promoting the sale of commercial products or services in so many ways, including the World Wide Web. For instance, advertising via the web has received much attention from people all over the world. Web advertising, in particular, has big implications to the global businesses because of wide accessibility strategies throughtout the world. Therefore, this study is carried out to identify the antecedents that influenced consumer’s attitudes towards Tourism in Malaysia web advertising that is widely available. Based on a review of the existing literature in a range of fields, this study proposes a conceptual model of the positive relationships between customer’s atitude with informativeness, entertainment, credibility, economic value, interactivity and materialism. The proposed conceptual model is developed based on the Elaboration Likehood (ELM). Tourism Malaysia strongly rides on its slogan ‘Malaysia Truly Asia” that signifies the ever-changing and growing needs for the future. Furthermore, Tourism Malaysia web advertising also can affect the consumer’s decision-making process and behavior. The researcher expects this research to make several theoretical, managerial and policy contributions. For instance, the tourism promotional board which wants to change the customer’s attitude needs to take into consideration the influence factors such as informativeness, entertainment, credibility, economic value, interactivity and materialism for the web adverstisement.